2006
DOI: 10.1002/mnfr.200600006
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin in experimental models

Abstract: The contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a prototype compound of a whole class of halogenated aromatic hydrocarbons termed 'dioxinlike' contaminants present in food, human tissue, mothers milk, and environmental samples. Among the various adverse effects caused by TCDD in animal experiments, its carcinogenic effects caused particular concern. In rodents, long-term TCDD treatment leads to the development of tumors of the liver, thyroid, lung, skin, oral cavity and other sites. The occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 94 publications
2
92
1
2
Order By: Relevance
“…TCDD (>99.5% pure) was obtained from Cambridge Isotope Laboratory (Andover, MA). [6, H]E 2 and [6,7-3 H]E 1 (specific activities of 51 and 58 Ci/ mmol, respectively) and [4][5][6][7][8][9][10][11][12][13][14] C]E 2 (specific activities of 55.1 mCi/mmol) were purchased from PerkinElmer Life Science Products (Boston, MA). All the organic solvents used in this study were of HPLC grade or better, and were obtained from Fisher Scientific (Atlanta, GA).…”
Section: Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…TCDD (>99.5% pure) was obtained from Cambridge Isotope Laboratory (Andover, MA). [6, H]E 2 and [6,7-3 H]E 1 (specific activities of 51 and 58 Ci/ mmol, respectively) and [4][5][6][7][8][9][10][11][12][13][14] C]E 2 (specific activities of 55.1 mCi/mmol) were purchased from PerkinElmer Life Science Products (Boston, MA). All the organic solvents used in this study were of HPLC grade or better, and were obtained from Fisher Scientific (Atlanta, GA).…”
Section: Chemicalsmentioning
confidence: 99%
“…In comparison, the data from earlier animal studies were clearer and more intriguing. While chronic administration of TCDD to female rats enhanced the tumor incidence in liver and also many other organ sites, this treatment inhibited the formation of spontaneous tumors in the uterus, mammary gland, and pituitary [11][12][13], which are target tissues for endogenous estrogens.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of the studies revealed that TCDD lead to DNA damage by the induction of oxidative stress (Hung et al, 2006;IIavarasi et al, 2011;Knerr and Schrenk, 2006). However, the mechanism by which SFN elevated TCDD-induced DNA damage remains unclear.…”
Section: Discussionmentioning
confidence: 99%